Non-pathogenic Escherichia coli Enhance Stx2a Production of E. coli O157:H7 Through Both bamA-Dependent and Independent Mechanisms - Xiaoli, Lingzi; Figler, Hillary M.; Goswami Banerjee, Kakolie; Hayes, Christopher S.; Dudley, Edward G. (Frontiers in Microbiology, 2018)
Intestinal colonization by the foodborne pathogen E. coli O157:H7 leads to serious disease symptoms, including hemolytic uremic syndrome (HUS) and hemorrhagic colitis (HC). Synthesis of one or more Shiga toxins (Stx) is essential for HUS and HC development. The genes encoding Stx, including Stx2a, are found within a lambdoid prophage integrated in the E. coli O157:H7 chromosome. Enhanced Stx2a expression was reported when specific nonpathogenic E. coli strains were co-cultured with E. coli O157:H7, and it was hypothesized that this phenotype required the nonpathogenic E. coli to be sensitive to stx-converting phage infection. We tested this hypothesis by generating phage resistant nonpathogenic E. coli strains where bamA (an essential gene and Stx phage receptor) was replaced with an ortholog from other species. Such heterologous gene replacement abolished the ability of the laboratory strain E. coli C600 to enhance toxin production when co-cultured with E. coli O157:H7 strain PA2, which belongs to the hypervirulent clade 8. The extracellular loops of BamA (loop 4, 6, 7) were further shown to be important for infection by stx2a-converting phages. However, similar gene replacement in another commensal E. coli, designated 1.1954, revealed a bamA-independent mechanism for toxin amplification. Toxin enhancement by 1.1954 was not the result of phage infection through an alternative receptor (LamB or FadL), lysogen formation by stx2a-converting phages, or the production of a secreted molecule. Collectively, these data suggest that nonpathogenic E. coli can enhance toxin production through at least two mechanisms.